On the Preconditioned Delayed Weighted Gradient Method - Aleixo, R.; Lara Urdaneta, H. (Trends in Computational and Applied Mathematics, 2023)
In this article a preconditioned version of the Delayed Weighted Gradient Method (DWGM) is presented and analyzed.  In addition to the convergence, some nice properties as  the A- orthogonality of the current transformed gradient with all the previous gradient vectors as well as finite convergence are demonstrated. Numerical experimentation is also offered, exposing the benefits of preconditioning.